Cross-country comparison: does social democratic party power increase an employee’s perceived employability? - Habicht, Isabel M. (Frontiers in Sociology, 2023)
Individuals strive to be highly employable, yet, we lack a uniform definition of ‘employability’. Within the labour market, employability can be seen as a product of individual human capital resources. However, this study argues that employability is also affected by the structure of the labour market and therefore also considers a country’s economic situation and political power to quantify employees’ perceived employability. Using data from the International Social Survey Programme, the Manifesto Project Dataset, and the International Labour Organization, this study uses a multilevel regression model with data from 30 countries. This paper disentangles the impact of individual careers and country policies (micro–macro linkage) on the perceived employability of their employees. At the individual level, initial education is the main predictor of employees’ current perceived employability, but vocational training is not. At the country level, the share of social democratic party power in each country, as a driver of active labour market policies, has a net effect on employee’s perceived employability, irrespective of their individual human capital investments. The generalisability of the findings is relevant to current debates about whether workers should become managers of their own careers or whether policymakers should take responsibility.